2021
DOI: 10.21273/jashs04954-20
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Key Floral Initiation Genes in Response to Plant Growth Regulator Application and Alternate Bearing in Pecan

Abstract: Regarding pecan (Carya illinoinensis), alternate bearing, which is a biennial fluctuation of crop yield, is a major hindrance for the pecan industry. Little is known about the internal cues that trigger pecan shoots to become reproductive. This 2-year study approached the mysteries of alternate bearing of pecan by determining whether pecan homologs of three genes known to control floral initiation in other species are expressed differently at various times of the growing season or in distinct plant tissues, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Gene specific primers and probes were designed for GI , MS2 , STM , KNAT6 , TFL1 and CAL-A ( Table 2 ) and synthesized by Integrated DNA Technologies (Coralville, IA) each with a unique fluorescent reporter dye. The ACTIN probe [ 14 ] was used as the housekeeping gene to normalize the qPCR analyses. Assays for each sample were performed in 3 technical and 3 biological replicates using iQ™ Multiplex Powermix (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Gene specific primers and probes were designed for GI , MS2 , STM , KNAT6 , TFL1 and CAL-A ( Table 2 ) and synthesized by Integrated DNA Technologies (Coralville, IA) each with a unique fluorescent reporter dye. The ACTIN probe [ 14 ] was used as the housekeeping gene to normalize the qPCR analyses. Assays for each sample were performed in 3 technical and 3 biological replicates using iQ™ Multiplex Powermix (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Differential expression studies have been previously reported for fruit and nut tree species for biotic stresses under field conditions [ 25 27 ]. Numerous differential expression studies have been done on C. illinoinensis in the past, most of which address horticultural questions [ 28 31 ]. Only recently has this method been used to examine biotic stress in pecan.…”
Section: Introductionmentioning
confidence: 99%